(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
One of the most visible manifestations of men’s and women’s power disparities is violence against women and girls. The analysis of statisticaldata and surveys reveals that violence against women in various forms is a global phenomenon that crosses across cultures, nations, and social and age groups. The core causes of violence against women, according to this paper, are prevalent gender norms and an asymmetrical power stability between men and women. The publication explains the international and regional human rights frameworks relating to gender-based violence, as well as the devastating impact of violence against women and girls on human development and how this links to the majority of the Millennium Development Goals. It is emphasized that gender stereotypes and the connection between the sexes must be addressed in order to prevent gender-based violence. As a result, collaborating with men and boys is just as crucial as assisting women and girls.